(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The legal environment for sexual coercion against children and victimization has undergone major changes in the last few years, with an increasing focus on victim protection and victim assistance. The aim of this study is to provide insight, through a case study, into different aspects of forensic psychological and psychiatric examinations of children in relation to the sexual coercion of minors and the circumstances of traumatization. Methodology: As minor victims and suspects are also subject to forensic examination in criminal expertise, a number of practical issues arise. In the case study presented here, the issue of child prostitution will be analyzed by outlining the life story of the 17-year-old subject, her current life situation, her actions, and her emotional factors. Findings: The case is representative of the seriousness of the problem, the victim’s vulnerability, her hopelessness, and the length of the criminal proceedings. A causal relationship between life events and current anxiety disorders and psychological instability is demonstrated. Value: Law enforcement professionals are often faced with the need to assign a forensic expert. Law enforcement training and clinical psychology and psychiatric professional competence represent significantly different knowledge. This study, through the presented expert tasks, provides useful assistance to law enforcement officers in the performance of their daily tasks.